Magnetoresistance based determination of basic parameters of minority charge carriers in solid matter - Uhryn, Y.O.; Peleshchak, R.M.; Brytan, V.B.; Velchenko, A.A. (Condensed Matter Physics, 2017)
Magnetoresistance as a tool of basic parameters determination of minority charge carriers and the ratio of
minority charge carriers conductivity to majority ones in solid matter has been considered within the framework
of the phenomenological two-band model. The criterion of the application of this model has been found. As
examples of these equations usage the conductor, semiconductor and superconductor have been introduced.
From the obtained temperature dependences of the aforementioned values in superconductor, a suppositi Запропоновано спосiб використання магнетоопору, як iнструмент для визначення основних параметрiв
носiїв заряду та вiдношення провiдностi неосновних носiїв заряду до основних в твердих тiлах на основi
аналiзу кривої магнетоопору в рамках феноменологiчної двозонної моделi. Встановлено критерiй застосовностi цiєї моделi. В ролi прикладiв застосування отриманих рiвнянь приведено провiдник, напiвпровiдник та надпровiдник. Зi знайдених температурних залежностей згаданих вище величин в надпровiдниках зроблено припущення про вирiшальну роль неосновних носiїв заряду у виникненнi надпровiдного
стану.